Catalysis of Thrombin Inhibition Provides an Index for Estimating the Antithrombotic Potential of Glycosaminoglycans in Rabbits - Fernandez, F A; Buchanan, M R; Hirsh, J; Fenton II, J W; Ofosu, F A (Thrombosis and Haemostasis, 1987)
Previous studies have demonstrated that standard anticoagulant tests are poor indices of the antithrombotic potential of glycosaminoglycans which are weak catalysts of the thrombinantithrombin III reaction. In this study we investigated whether the catalysis of thrombin inhibition by plasma could serve as a reliable index for assessing the antithrombotic effectiveness of glycosaminoglycans. Equal volumes of 125I-thrombin and control or test plasma were incubated for up to 10 min at 37° C. Inactivation of thrombin was then determined after 7.9% SDS-polyacrylamide gel electrophoresis and subsequent autoradiography. Increasing concentrations of heparin (>0.066 μg/mL or 0.01 USP units/mL) and dermatan sulfate (>0.1 μg/mL) could be readily demonstrated in undiluted plasma by enhanced formation of complexes of thrombin with antithrombin III and heparin cofactor II respectively. However, the detection of any catalytic effect of the two glycosaminoglycans decreased significantly with increasing plasma dilutions. When ex vivo plasmas obtained from rabbits that had been injected with the minimum dose of any one of seven glycosaminoglycans required to achieve their optimal antithrombotic effect were assessed for their ability to catalyse thrombin inhibition, there was approximately a 2-fold increase in the amount of thrombin inactivated 30 s after the thrombin had been added to the plasma. The enhanced inhibition of thrombin was achieved by catalysis of antithrombin III and/or heparin cofactor II activities. These results suggest that measurement of the catalysis of thrombin inactivation in undiluted plasma is a sensitive and reliable index for estimating the antithrombotic potential of glycosaminoglycans in rabbits.
Keywords: Antithrombotic; Heparin cofactor II; Antithrombin III; Thrombin inhibition